(untitled) (Global Journal of Human-Social Science, 2024)
This study focuses on the Brussels Effect and how its influence can shape other countries and blocs regarding global sustainability To examine the Brussels Effect as a mechanism the parameter of governance at the legislative moment was used as well as the principles of a high level of ecological protection Leaving no one behind European ecological responsibility and non-retrogression Sustainable policies in their legislative stages were studied through the dogmatic teleological methodology and the post-positivist application of NEPE The proposed examination highlighted the EU s important role in environmental sustainability policies as it aims to implement sustainable standards globally However side effects can arise if principles such as NEPE and Leave No One Behind are not recognised in legislative governance